Agricultural Implications of the Fukushima Nuclear Accident 2013
DOI: 10.1007/978-4-431-54328-2_16
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and Transportation Dynamics of 137Cs Deposited on the Forested Area in Fukushima After the Fukushima Daiichi Nuclear Power Plant Accident in March 2011

Abstract: A massive amount of radioactive substances, including cesium-137 ( 137 Cs), emitted from the disabled nuclear power plant has deposited on the forested areas in the northeastern region of Honshu Island, Japan after the Fukushima Daiichi nuclear power plant accident. Forests in these regions are particularly important not only for the forest products industry but also for source areas of drinking water and for residential environments. To clarify the mechanisms of diffusion and export of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Our four-year monitoring study since early 2012 at a forested headwater catchment in the northern part of Fukushima have demonstrated that radiocesium movement has been most drastic during the early years after the accident (Ohte et al 2013(Ohte et al , 2016. Observed results have shown that radiocesium has continuously moved from the forest canopies to the forest floor with throughfall, stemflow and litter fall (Endo et al 2015).…”
Section: Introductionmentioning
confidence: 81%
“…Our four-year monitoring study since early 2012 at a forested headwater catchment in the northern part of Fukushima have demonstrated that radiocesium movement has been most drastic during the early years after the accident (Ohte et al 2013(Ohte et al , 2016. Observed results have shown that radiocesium has continuously moved from the forest canopies to the forest floor with throughfall, stemflow and litter fall (Endo et al 2015).…”
Section: Introductionmentioning
confidence: 81%
“…Moreover, standing trees in the main forest were cut down and sampled in November of both 2012 and 2013 to estimate the amount of radioactive cesium buildup above the ground. The samples were divided into live leaves, branches, and trunks (bark, sapwood, and heartwood) to measure the radioactive cesium concentration 10,11) .…”
Section: Survey Methodsmentioning
confidence: 99%
“…This paper reports the survey results using data obtained by the end of FY2014 to consider necessary surveys and measures for the future. It may be noted that most of the findings have already been published in the references [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to investigate the major pathways of radiocesium transfer in the forest, such as physical transportation via hydrological processes and biological transfer through the food web in terrestrial and aquatic ecosystems. To describe the current status and to examine the hypothesized mechanisms mentioned above, catchment scale biogeochemical observations have been conducted in the northern part of the Fukushima prefecture since August 2012 (Ohte et al 2012(Ohte et al , 2013, and they currently continue (February 2015). Here, we report the latest results and discuss the future perspectives for monitoring radiocesium levels in Fukushima forests.…”
Section: Introductionmentioning
confidence: 99%